Existence of solution to transpiration control problem. (1992) - Zhu, Guanstian; Wu, Jingang; Liang, Benzhong; Ji, Xinhua; Yang, Xueshi
Abstract : Transpiration control can avoid change of the shape of a high-speed vehicle resulting from ablation of the nose, therefore also can avoid the change of the performance of Aerodynamics. Hence it is of practical importance. A set of mathematical equations and their boundary conditions are founded and justified by an example of non-ablation calculation in reference [1]. In [2], the ablation model is studied by the method of finite differences, the applicable margin of the equations is estimated through numerical calculation, and the dynamic responses of control parameters are analyzed numerically. In this paper we prove that the solution to transpiration control problem given in [1] exists uniquely under the assumption that the given conditions (i.e. given functions) are continuous.